Nina's treasures - Czernecki, Stefan; Rhodes, Timothy (New York : Hyperion Paperbacks for Children, 1994)
When Katerina runs out of food at the end of winter, her beloved hen Nina saves them both by laying marvelous multicolored eggs.
"Originally published by Sterling Publishing Co., Inc., New York, New York"--verso of t. p.
4.5
K-3
K-3
Horn Book
Keywords: Chickens -- Fiction; Eggs -- Fiction; Chickens -- Fiction; Eggs -- Fiction; Ukrainian art -- Fiction